Airway Management in Patient Trauma Maxillofacialwith Mild Head Injury, Open Fracture Depressed, and Skull Base Fracture - Sudjud, Reza Widianto; , suwarman; Patrianingrum, Meilani (Majalah Anestesia dan Critical Care, 2015)
Establishing a secure airway in a trauma patient is essentials. Any law in airway management may lead to gravemorbidity and mortality. Maxillofacial trauma presents a complex problem with regard to the patient’s airway.Moreover, this patient sometimes accompanied with head injury and fracture cervical.In this case report, wereported male, 41 years old, came to the hospital Hasan Sadikin General Hospital with complaints wounds in thehead and face as a result of trafic accidents. This patient suffered trauma maksilofasialis with addition of minorhead injuries, open fractures depressed more than one tabula, incomplete cervical injury and skull base fractures.Management airway in this patient is spontaneous breathing that is achieved by administering propofol and gasgradually Sevolurane inhalation. Meanwhile, to prevent hemodynamic disturbances during laryngoscopy Fentanylwas given. The manual in-line stabilization was performed to prevent neck lexion when laryngoscopy intubation.In cases where airway is dificult to manage, intubation technique chosen is the one that anesthesiologist most feltcomfortable. Both of these factors are more relevant than the choice of technology.